TIPOLOGI INTERREGIONALISME UNI EROPA DALAM MERESPONS PENULARAN PANDEMI COVID-19 DI EROPA - Bustami, Sirwan Yazid (BHUVANA: Journal of Global Studies, 2023)
Globalization of the Covid-19 pandemic has caused a very rapid contagion effect between regions around the world and has created a multidimensional crisis in European Union countries, so an interregionalism approach is needed. This study aims to analyze the typology of European Union interregionalism in response to the contagion of Covid-19 pandemic in Europe. By using analytical descriptive methods combined with Mathew Doidge’s theory of interregionalism, Heiner Hänggi’s typological concepts of interregionalism, and data analysis techniques using Miles and Huberman’s models, this study found that European Union adheres to three types of interregionalism, namely group-to-group interregionalism, biregional-transregional interregionalism, and hybrid interregionalism. Group-to-group interregionalism is carried out by building dialogues and partnership cooperations between regions related to economic recovery and capacity building to strengthen the governance of Covid-19 pandemic with ASEAN, African Union, and Mercosur. Meanwhile, biregional-transregional interregionalism is carried out by building dialogues and partnership cooperations between regions related to capacity building to strengthen the governance of the Covid-19 pandemic with ASEM countries. Finally, hybrid interregionalism is carried out by building dialogues and bilateral partnership cooperations related to economic recovery and global health with the United States, China, Japan, Turkey, and Canada. European Union interregionalism in response to contagion effect of Covid-19 pandemic functions as a means of power balancing, collective identity formation, agenda setting, institution building, and rationalizing.